Identification of homologs of the Chlamydia trachomatis effector CteG reveals a family of Chlamydiaceae type III secreted proteins that can be delivered into host cells - Pereira, Inês Serrano (2024)
Funding Information: We are grateful to Mariana Mend\u00E3o for the construction of plasmids, and to our colleagues Agathe Subtil, Ian Clarke, Mar\u00EDa Rosa Vergara, and Nicole Borel for generously providing DNA of several Chlamydia species and antibodies. Funding Information: This work was supported by Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia (FCT) through grant PTDC/BIA-MIC/28503/2017, and in the scope of the projects UIDP/04378/2020 and UIDB/04378/2020 of the Research Unit on Applied Molecular Biosciences \u2013 UCIBIO, and LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy - i4HB. ISP and MPL were supported by PhD fellowships SFRH/BD/129756/2017 and SFRH/BD/144284/2019, respectively, also funded by FCT. Open access funding provided by FCT|FCCN (b-on) Publisher Copyright: © The Author(s) 2024.